2022
DOI: 10.3390/su14052547
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness in Health Education: From Physical to Virtual Presence during the Pandemic, an Anthropological Study in Spain

Abstract: Research on traditional mindfulness-based interventions supports the position that they are effective in treating psychological problems and benefiting healthy people. However, more research is needed on the effectiveness of online interventions, a field that is growing and developing rapidly, especially with the onset of the pandemic, as many meditation groups have moved into cyberspace. There is little research on the difficulties that these groups face and the effectiveness of online mindfulness practice. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Although mindfulness is a concept that originated in philosophy and religion studies, it has been found to have widespread application in psychology (Zheng et al , 2022), the health-care sector (Tellez Infantes et al , 2022), sports (Wang et al , 2023; Goisbault et al , 2022) and event economics (Brunelle and Grossman, 2022; Hirsch and Chen, 2022). As a result, mindfulness is believed to cause a fundamental shift in perspective and subsequent positive outcomes through self-regulation, cognition, emotion and behavioral flexibility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although mindfulness is a concept that originated in philosophy and religion studies, it has been found to have widespread application in psychology (Zheng et al , 2022), the health-care sector (Tellez Infantes et al , 2022), sports (Wang et al , 2023; Goisbault et al , 2022) and event economics (Brunelle and Grossman, 2022; Hirsch and Chen, 2022). As a result, mindfulness is believed to cause a fundamental shift in perspective and subsequent positive outcomes through self-regulation, cognition, emotion and behavioral flexibility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mindfulness is another emerging topic when it comes to the study of brainwaves, said to have important implication in areas such as social behavior or mental health. In the East, mindfulness meditation has been practiced in association with various Buddhist schools for more than two millennia as a means of enhancing personal and societal peace [7]. After extensive neurological research, a new understanding of human nature that encourages the achievement of individual potential at all levels emerged, showing clear positive implications of this practice.…”
Section: Introductionmentioning
confidence: 99%
“…In pre-COVID 19 times, many organisations and individuals have already been aware of the benefits of exercising to be mindful and participating in mindful training programs in support of enhancing employee's health and well-being [1,2]. However, with the extensive lockdown in the midst of COVID-19, and likely increased adaption of work-from-home (WFH) arrangements by organisations, it is ambiguous whether practicing mindfulness individually and participating in mindfulness training programs organised by workplaces can assist employees in their effort to balance work-life and reduces stress arising from extensive WFH setting, whilst accommodating the needs to look after children and care for elderly family members at home, especially for women.…”
Section: Introductionmentioning
confidence: 99%